Testimony of Jonas Senkus about activity of Red terror museum - Anušauskas, Arvydas (Genocidas ir rezistencija, 2007)
During the German occupation, the Museum of the Red Terror was established to collect testimonies of the horrors of the Soviet occupation in 1941–1944, as well as authentic Soviet security documents, which were even planned to be displayed in an exhibition in the West. However, the Germans also wanted to use it for anti-Soviet propaganda